2021
DOI: 10.3389/fnut.2021.758661
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Dietary Quality During Initial and Later Stages of the COVID-19 Pandemic in Mexico

Abstract: Background: The COVID-19 pandemic disrupted the global economy and modified lifestyles. The aim of our study was to identify factors associated with dietary quality, and their frequency, in Mexican adults at the initial and later stages of the pandemic.Methods: Two online surveys were conducted between June and July 2020 (n = 3,131) and between November and December 2020 (n = 1,703 including non-participants from 1st round). A diet quality score was estimated using a short instrument to measure the consumption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…This may occur through elevation in cortisol associated with stress with subsequent effects on brain structures, including the hippocampus [ 43 ]. Food insecurity is also related to lower diet quality and nutrient intake [ 44 ], including in Mexican samples [ 45 , 46 ], as individuals may respond to limited food access by opting for foods that are cheaper, but not necessarily nutritious. High quality diets have been associated with better cognitive outcomes, including lower risk of Alzheimer’s Disease [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may occur through elevation in cortisol associated with stress with subsequent effects on brain structures, including the hippocampus [ 43 ]. Food insecurity is also related to lower diet quality and nutrient intake [ 44 ], including in Mexican samples [ 45 , 46 ], as individuals may respond to limited food access by opting for foods that are cheaper, but not necessarily nutritious. High quality diets have been associated with better cognitive outcomes, including lower risk of Alzheimer’s Disease [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is speculated that working from home provided them with more time to prepare home-cooked meals. Similarly, Mexican adults perceived that their dietary habits improved during the pandemic due to working from home and eating homemade food ( 54 ). Moreover, a cohort study concluded that eating home-cooked meals was associated with older age, higher socioeconomic status, and not working overtime ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the sociodemographic characteristics influenced food and beverage consumption behavior during the pandemic [64,65]. In terms of gender, since, in our study, zero are male and one is female, being male positively influences the online grocery shopping experience.…”
Section: Discussionmentioning
confidence: 58%